(untitled) (Experimental biology, 2015)
Hydrobiological indices characterize the quality of water as the habitat of living organisms that inhabit the pond. Organisms have different reactions to the impact of pollutants. This allows using the methods bioindication assess the degree of water pollution, and more precisely the degree of harm to their organism, the cumulative effects of all pollutants present in water. The results obtained have led to the development of principles of organization of biomonitoring.